QUALITY OF LIFE ASSESSMENT IN THE HEART FAILURE PATIENTS TAKING STANDARD MEDICAL CARE IN TEACHING HOSPITAL: Quality of life in Heart failure - PRIYANKA SHARMa; MD SAYEED AKHTAR; FAUZIA TABASSUM; NIMISHA TANDON; ANSHU NANDA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This study was aimed to assess the quality of life (QoL) of the subjects having congestive heart failure (HF) under different domains of life, such as physical, psychological, and social domains, and they started taking the standard care treatment. Methods: The questionnaire-based prospective study was designed to assess the effects of the HF in different domains of life such as social, psychological, physical, or mental. After getting consent from the subjects, health questionnaire was provided to a total of 60 subjects. Results: We found drastic improvements in 24% of total HF cases in terms of physical debility, whereas only 15% patients reported none of the complications during taking standard care therapy. Total 32.5% patients aware of the treatment took and to whom contact in an emergency. Psychological disturbances and life satisfaction were observed in 16.66% and 33.33% cases suffering from HF. Patient compliance means personal life, as well as medication adherence, was observed in only 53.33%. Conclusions: The results obtained from the responses given by the patients in the health questionnaires demonstrated that the HF patients’ needs awareness regarding the therapy precautions that improving the QoL of patients.